High power = Motivation? Low power = Situation? The impact of power, power stability and power motivation on risk-taking. - Hiemer, Julia; Abele, Andrea E. (Personality and individual differences, 2012)
The present research analyzes the influence of situational (role stability vs. instability) and personal (power motivation) variables on risk-taking behaviour of people with low vs. high power. We predicted that low power people are mainly influenced by the situation, whereas high power people also act in accord with their power motivation. We independently measured participants’ power motivation and later conducted a 2 (power role: high vs. low) × 2 (situation: stable vs. unstable role) experiment in which we assessed risk-taking behaviour in the Balloon Analogue Risk Task (BART; Lejuez et al., 2002).We also ran a control group without role assignment. Supporting our hypotheses, risk-taking behaviour of people with low power was influenced by the situation, but not by power motivation, whereas risk-taking behaviour of powerful people was influenced by both sources. Control group’s risk-taking was somewhat influenced by power motivation. (PsycINFO Database Record (c) 2012 APA, all rights reserved)
Keywords: power stability; power motivation; risk taking behavior; role stability vs instability; situational variable